Efficacy of Methylprednisolone in Acute Respiratory Distress Syndrome- COVID-19 Middle Euphrates Patients (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background:   The coronavirus disease 2019 was initially identified in Wuhan, the Chinese province of Hubei, in December 2019, and it quickly spread to other parts of the world.Objective: To assess the efficacy of MP in ARDS COVID-19 patients who admitted to ICU.                                                      Patients and Methods: Prospective cohort study, the data collection was among COVID 19 positive patients with severe acute respiratory syndrome attending the Intensive care unit One-hundred patients were included in this study: MP treated group included forty patients who exposed to high doses of MP 1 gm first day then 500 mg for other 4 days with standard treatment for COVID 19.Non MP treated group included sixty patients with standard care for COVID 19 alone.Results:A total of 100 patients with ARDS-COVID 19 positive were included in this study (40 MP treated and 60 non MP treated control group). The outcome for both group after 5 days has shown that; in exposed group: (27) 67.5 % of patients were improved, (7)  17.5 %of patients were worsen and (6) 15 %of patients died. In non MP treated group: 21.7 %of patients were improved, ( 40)  66.7 %of patients were worsen and(7) 11.7 %of patients were died and there were a significant association in the outcome and MP expose.Conclusion: In patients with ARDS COVID 19 positive, early administration of pulse dose of methylprednisolone was associated with remarkable improvement of general condition, vital signs and SPO2 ,and inflammatory markers .